132k views
1 vote
k(x) = -x^2-2x+3Solve with:k(sq root 2)k(a+2)k(-x)k(x^2)The negatives are giving me a problem. Thank you

User Fady
by
5.2k points

1 Answer

1 vote

To answer this question, we need to evaluate the function:


k(x)=-x^2-2x+3

Evaluating the function for x = √2

We can proceed as follows:


k(\sqrt[]{2})=-(\sqrt[]{2})^2-2(\sqrt[]{2})+3=-(2^{(1)/(2)})^2-2\sqrt[]{2}+3
k(\sqrt[]{2})=-(2^{(2)/(2)})-2\sqrt[]{2}+3=-(2)-2\sqrt[]{2}+3=-2+3-2\sqrt[]{2}
k(\sqrt[]{2})=1-2\sqrt[]{2}

We need to remember above that:


\sqrt[]{n}=n^{(1)/(2)}

Evaluating the function for x = a + 2

We can proceed as follows:


k(a+2)=-(a+2)^2-2(a+2)+3
(a+2)^2=a^2+2(a)(2)+2^2=a^2+4a+4

Then, we have:


k(a+2)=-(a^2+4a+4)-2(a)-2(2)+3
k(a+2)=-a^2-4a-4-2a-4+3

Now, we need to add like terms as follows:


k(a+2)=-a^2-4a-2a-4-4+3
k(a+2)=-a^2-6a-8+3\Rightarrow k(a+2)=-a^2-6a-5

Therefore


k(a+2)=-a^2-6a-5

Evaluating the function for x = -x

We have:


k(-x)=-(-x)^2-2(-x)+3
(-x)^2=(-x)(-x)=x^2
k(-x)=-x^2+2x+3

Evaluating the function for x = x²

We can proceed similarly:


k(x^2)=-(x^2)^2-2(x^2)+3=-(x^4)-2x^2+3

Therefore, we have:


k(x^2)=-x^4-2x^2+3

In summary, we have that:


k(\sqrt[]{2})=1-2\sqrt[]{2}\approx-1.82842712475
k(a+2)=-a^2-6a-5
k(-x)=-x^2+2x+3
k(x^2)=-x^4-2x^2+3

User Beikeni
by
5.8k points